ANALYSIS OF EXTERNAL BUSINESS COMMUNICATION IMPLEMENTATION PT UNILEVER INDONESIA - Yoga Bagus Pambudi (Business Journal : Jurnal Bisnis Dan Sosial, 2022)
The purpose of this study is to find out how PT Unilever Indonesia Tbk applies the scope of external business communication in enlarging its market prey. The method used in this study is a literature review with the approach taken in this study, namely collecting as many sources of information as possible including credible articles and books. Based on the analysis, Unilever was very concerned about various things before starting to acquire the company. This was done because Unilever wanted to stay on the main line, namely providing Fast Moving Customer Goods (FMCG) products.